Effect of Different Admixtures on Mechanical Properties of Concrete Paving Block: A Comparative Study - Asif Hossain; Md. Akhter Hossain (Nusa Putra University, 2024)
Ever since their introduction nearly a century ago, concrete paving blocks have become increasingly common. They evolved into an alternative to burned clay brick and natural stone. Concrete paving blocks are used to lay down areas for vehicles and pedestrians as well. Durability is one of the most crucial elements in the production of high-quality concrete paving blocks. The aim of this study is to optimize the mechanical properties of concrete paving block units by experimenting with different admixtures. Compressive strength, water absorption, oven dry density, and drying shrinkage are among the attributes that were evaluated. The cost of production was also contrasted with and without the use of an admixture to achieve a comparable compressive strength. The results showed that admixtures could be used to produce high early strength units, and this was considered to be an economical factor in the production of concrete paving block units. At all ages, the use of admixtures increased these units' compressive strength by 30–40%. Although they did slightly increase density, additives also decreased the absorption and drying shrinkage of concrete paving block units.